Newsprint from Blue Gum (Eucalyptus globulus Labill.) and Wattle Wood (acacia Decurrens Willd.) - Brat, R. V.; Virmani, K. C. (Indian Forester, 1957)
Experiments on the preparation of ground wood pulps from blue gum (Eucalyptus glabulus Labill.) and waattle wood (Acacia decurrens Willd.) under various conditions of grinding are described. Newsprint was prepared on the pilot plant paper machine of this Institute from a furnish containing 76% of blue gum groundwood pulp ( bleached) and 24% of bamboo sUlphate pulp (bleached). A sample of the newsprint is appended. Newsprint was also made on the pilot plant from a mixture of 75% of wattle groundwood pulp ( bleached) and 25% of bamboo Sulphate pulp (bleached). A sample of this newsprint is also appended.